Oil Price Shock and Macroeconomic Performance in Nigeria: Implication on Employment - Asaleye, Abiola John; Aremu, Charity; Lawal, Adedoyin Isola; Ogundipe, Adeyemi A.; Inegbedion, Henry; Popoola, Olabisi; Sunday, Adewara; Obasaju, Olusegun Barnabas (International Journal of Energy Economics and Policy, 2019)
Reduction in oil price in the international market, coupled high demand of foreign goods and wide swings of oil prices in the international market has posed different challenges for policies to promote growth and development. This study investigates the impact of oil shock on macroeconomic performance in Nigeria using Structural Vector Autoregression and normalized equation was used to establish the long-run equation. Evidence from the long-run relationship showed that employment has a negative relationship with aggregated output, exchange rate and oil prices. The interest rate and consumer price index has a positive relationship with employment. Variation in oil shock affects most of the macroeconomic variables. More explicitly, the oil price shock shows more variation across the time horizon for employment. The consequence of the result is that dependence on the oil sector has not promoted employment generation over time; there is a need to consider an alternative means to ensure sustainable growth and development. Keywords: Oil Price, Employment, Macroeconomic Performance JEL Classifications: F62, Q43, Q52 DOI: https://doi.org/10.32479/ijeep.7768